Pengetahuan Orang Tua Pada Anak Sekolah Dasar Terhadap Kasus Kesehatan Persistensi - Rosdiana, Rosdiana; Djunaedi, Djunaedi; Aditia, Donny; Sapnita, Sapnita; Nurambiya, Nurambiya (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
School-age children, especially children of primary school age (6-12 years) are a group that is vulnerable to dental and oral diseases because it is during this period that milk teeth begin to fall out one by one and are replaced by permanent teeth, with variations in milk teeth and permanent teeth together. in the mouth, marking the period of mixed dentition in children. Elementary school-age children are the mixed dentition period, that is, the transitional period when milk teeth fall out and permanent teeth grow and are an age that is considered vulnerable to dental and oral diseases. The purpose of this research is to explain the knowledge of parents in elementary school children with persistence cases. The type of research used is a literature study. The literature study method is a series of activities related to methods of collecting library data, reading and taking notes, and managing research materials. Results and conclusions that 1. Parents' knowledge of elementary school children with persistent cases is included in the less category where the better the knowledge the lower the child will experience tooth persistence. 2. Parents' knowledge will influence children's attitudes and behavior to maintain healthy teeth and mouth. Lack of parental knowledge due to lack of education. 3. Tooth persistence in children who are not treated immediately will cause other dental problems such as malocclusion, ectopic eruption and impaction. Tooth persistence in children can be prevented if parents have more knowledge about tooth persistence.